MTHFR C677T and MTR A2756G gene polymorphism in neural tube defect patients and its association with red blood cell folate level in Eastern Indian Population - Rekha Kumari; Santosh Kumar; Vinit Kumar Thakur; Kalpana Singh; Uday Kumar (Wolters Kluwer Medknow Publications, 2022)
Introduction: Single-nucleotide polymorphism (SNP) is a single-nucleotide change in a deoxyribose nucleic acid (DNA) sequence that occurs in >1% of population. Methylene tetra hydro folate reductase (MTHFR) C677T (rs1801133) and methionine synthase enzyme (MTR) A2756G (rs1805087) are two such SNPs occurring in coding sequence of the respective genes, which are frequently seen with neural tube defects (NTDs). MTHFR and MTR genes are involved in folate metabolism. The folate level in the course of pregnancy is treated as vital in the etiopathogenesis of NTDs. This study aims to explore the association of SNPs of both genes and red blood cell (RBC) folate levels in the predisposition to NTDs. Aims and Objective: The purpose of this investigation was to determine the relationship of NTDs with polymorphisms in MTHFR and MTR genotype and to estimate and compare the RBC folate levels in NTD patients and controls. Materials and Methods: A total of 397 individuals were enrolled (163 patients and 234 controls) for this observational study. Genotyping to find out MTHFR C677T and MTR A2756G was performed by polymerase chain reaction-restriction fragment length polymorphism technique from DNA extracted from the subject's blood. RBC folate level was estimated by chemiluminescence immunoassay method with the same blood sample. Results: The total RBC folate levels were significantly less among cases compared to controls (P = 0.020). A significant difference for RBC folate was observed between case and control groups of various genotypes of MTHFR C677T, except heterozygote CT (P = 0.459). Among MTR A2756G, genotypes with only homozygous AA have significant difference (P = 0.003) for RBC folate levels. Among different types of NTDs, there were no significant differences for RBC folate levels. Among MTHFR C677T, T allele possessed 1.9 times risk compared to C allele for the occurrence of NTDs. In MTR A2756G polymorphism, the odds of developing NTDs were 1.6 times in heterozygous AG compared to homozygous AA. Similarly, the risk for NTDs was three times higher in subjects with both heterozygous AG and CT genotypes compared to wild-type homozygous AA and CC genotypes. Conclusion: The total RBC folate levels were significantly less among cases compared to controls, and the genotypes had no such effect in decrease in RBC folate levels. The presence of mutant allele in homozygous or heterozygous condition for both SNPs had increased risk associated with NTDs.